h - Kopp, P. E., 1944-; ebrary, Inc. (Cambridge [England] ; New York : Cambridge University Press, 2011)
c
c
Machine generated contents note: Preface; 1. Probability and measure; 2. Measures and distribution functions; 3. Measurable functions/random variables; 4. Integration and expectation; 5. Lp-spaces and conditional expectation; 6. Discrete-time martingales; 7. Brownian motion; 8. Stochastic integrals; Bibliography; Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Measure theory -- Textbooks; Electronic books